POSHAN’s abstract digest on maternal and child nutrition research - Issue 48 - Avula, Rasmi (International Food Policy Research Institute, 2023)
The 48th issue of Abstract Digest features studies on anemia highlighting trends, inequities, and determinants of anemia among various population groups. Another study examined micronutrient deficiencies and their association with cognitive function among children and adolescents. This issue also includes the latest Lancet 2023 Breastfeeding Series editorial and three-papers that outline the multifaceted and highly effective strategies used by commercial formula manufacturers to target parents, health-care professionals, and policy-makers. Other studies included are on patterns in the prevalence of unvaccinated children, variations in measures of poverty, and an assessment of progress on the sustainable development goals. Another study examined the validity of maternal reports of receiving counseling on infant and young child feeding, and yet another one examined utilization of systematic review-based evidence in formulating guidelines for the National Health Programme.